2009
DOI: 10.1530/eje-08-0900
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the ADIPOR2 gene is associated with liver fat content and its surrogate markers in three independent cohorts

Abstract: Aims: We investigated whether polymorphisms in candidate genes involved in lipid metabolism and type 2 diabetes are related to liver fat content. Methods: Liver fat content was measured using proton magnetic resonance spectroscopy ( 1 H-MRS) in 302 Finns, in whom single nucleotide polymorphisms (SNPs) in acyl-CoA synthetase long-chain family member 4 (ACSL4), adiponectin receptors 1 and 2 (ADIPOR1 and ADIPOR2), and the three peroxisome proliferator-activated receptors (PPARA, PPARD, and PPARG) were analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 50 publications
4
43
0
2
Order By: Relevance
“…2 Carriers of the PNPLA3 I148M allele have more hepatic fat 4,13 in the liver, and in our obese cohort they have increased circulating levels of ALT and AST. We went on to examine whether carriers of the 148M allele were more insulin resistant or had any impairment in glucose tolerance.…”
mentioning
confidence: 59%
“…2 Carriers of the PNPLA3 I148M allele have more hepatic fat 4,13 in the liver, and in our obese cohort they have increased circulating levels of ALT and AST. We went on to examine whether carriers of the 148M allele were more insulin resistant or had any impairment in glucose tolerance.…”
mentioning
confidence: 59%
“…Furthermore, based on correlative studies, ACSL4 has been proposed to promote hepatic TAG synthesis ( 35,36 ), to contribute to human hepatocellular carcinoma and adenocarcinoma ( 37,38 ), and to have important effects in cognitive function and neuromuscular disease ( 15,(39)(40)(41). ACSL4 gene expression was also found to be signifi cantly upregulated in livers of insulin-resistant human subjects with nonalcoholic fatty liver disease ( 42 ), and recently, a polymorphism in ACSL4 was found to be signifi cantly associated with liver fat content ( 36 ). The biological function of ACSL4 in SMCs and other vascular cells has been unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, adiponectin signalling alleviated or prevented NASH in mice, 33,34 and associations of hypoadiponectinaemia with fatty liver and/or NASH have been reported in humans. 35,36 Furthermore, genetic studies revealed associations of ADIPOR1/2 with IR and liver fat content, 37,38 and overexpression of ADIPOR1/2 has been shown to potentiate subeffective doses of adiponectin. 39 We therefore suggest that the increased ADIPOR1/2 mRNA expression in obese, insulin-resistant subjects represents a mechanism that may partially compensate for reduced plasma adiponectin.…”
Section: Discussionmentioning
confidence: 99%